The FTO rs9939609 polymorphism is associated with short leukocyte telomere length in nonobese individuals. Issue 30 (July 2017) - Yu, Ji Hee; Baik, Inkyung; Cho, Hyun Joo; Seo, Ji A.; Kim, Sin Gon; Choi, Kyung Mook; Baik, Sei Hyun; Choi, Dong Seop; Shin, Chol; Kim, Nan Hee
Abstract : Abstract: The fat mass and obesity-associated (FTO) rs9939609 polymorphism have been associated with the increased metabolic risk and mortality, irrespective of obesity. The mechanism underlying this association is not known. We aimed to evaluate whether the FTO rs9939609 risk variant is independently associated with metabolic risk factors and/or leukocyte telomere length (LTL). We further aimed to investigate whether this relationship is modified by obesity status. A total of 2133 participants were recruited from the Korean Genome and Epidemiology Study. LTL was measured using the real-time quantitative polymerase chain reaction methodology. The FTO rs9939609 polymorphism was genotyped using DNA samples collected at baseline. The proportions of the TT, TA, and AA genotypes were 76.7%, 21.5%, and 1.8%, respectively, and obese subjects comprised 44.5% of the total subjects. Among the 1184 nonobese subjects, body mass index, waist circumference, and visceral fat area were higher in subjects with the FTO risk allele than in noncarriers. In contrast, only high-sensitive C-reactive protein level was associated with the FTO risk allele in the obese subjects. LTL was significantly shorter in carriers of the FTO risk allele compared with noncarriers after controlling for several confounding factors ( P  < .01). Of particular note, this significant association between the FTO risk allele and LTL appeared only in nonobese subjects ( P  = .03). Multivariate linear regression analyses identified older age, low high-density lipoprotein cholesterol level, and the presence of the FTO risk allele as independent risk factors affecting LTL. This finding was evident only in nonobese subjects. The FTO rs9939609 polymorphism is an independent risk factor for obesity and also for biological aging in the nonobese population. Abstract : Supplemental Digital Content is available in the text